Supporting the Implementation of Residential Heating Measures in Bulgaria’s National Air Quality Improvement Program and National Air Pollution Control Program - World Bank (World Bank, Washington, DC, 2020)
These programs have been prepared by the Government of Bulgaria (GoB) with technical support by the World Bank. In the course of the work it became clear that national and local institutions would face multi- faceted challenges in implementing the NAQIP and NAPCP, relating mainly to overcoming financial, administrative, and technical difficulties. The swift evolution of EU policy frameworks for countering climate change, improving energy security, reducing energy poverty, as well as the need to improve health and wellbeing in Bulgaria, add to those challenges though they may be regarded instead as presenting significant economic opportunities. The NAQIP proposes measures for phasing out the use of thermally inefficient, polluting old stoves and boilers that burn solid fuels, replacing them with cleaner, more efficient heating arrangements. It is expected that the measures will reduce PM10 emissions from the residential heating sector by about 78 percent. Other measures target the road transport sector though its contribution to local emissions is minor in comparison. The NAPCP focuses on meeting air pollutant emission targets for 2030 as required in the Revised NECD. NAQIP measures to reduce PM10 emissions from the residential heating sector are incorporated in full in the NAPCP. Other sectors where policies and measures to reduce emissions were considered have included large combustion plants in the power generation and industrial sectors, road transport, agriculture, and industrial processes. The preparation of these two programs was complemented by capacity strengthening, including the development of tools to help municipalities undertake essential planning and project preparation. All guidance documentation to accompany the tools were collated to form a Resource Toolkit. Communication and coordination issues were also tackled in the engagement.